Alternanthera sessilis: a review of literature on the phytoconstituents, traditional usage and pharmacological activities of green and red cultivar - Ragavan, Omilla; Chan, Sze Cheng; Goh, Yi En; Lim, Vuanghao; Yong, Yoke Keong (Wolters Kluwer Medknow Publications, 2023)
The weed Alternanthera sessilis, having Green (ASG) and Red (ASR) cultivars, is a member of the Amaranthaceae. Both cultivars are known to possess high medicinal and nutraceutical values as they are widely utilized in traditional medicine. Populations from various Asian regions commonly consume this medicinal weed as part of diet and as therapeutic agent. In general, both cultivars have been employed for treating a broad range of human ailments including cardiovascular diseases, diabetes, hypertension, and inflammatory disorders such as asthma, bronchitis and hepatitis apart from its administration as a painkiller. Following its ethnomedicinal uses, an attempt was made to review and consolidate the phytochemical constituents of ASG and ASR discovered from previous studies that utilized advanced technologies, respective traditional application among different ethnicities of Asia and their established pharmacological properties. All the information in this study was acquired through a literature search of research databases, namely ScienceDirect, Scopus, PubMed and Google Scholar using keywords such as Alternanthera sessilis, Alternanthera sessilis red, dwarf copperleaf and sessile joyweed. The results of each study were reviewed to identify its relevance and the cultivar that was being investigated. All relevant studies were collected and its subsequent results were reported and discussed to provide insights into the health enhancing qualities of ASG and ASR. Inspection of phytoconstituents in ASG and ASR showed the presence of polyphenol, flavonoid, carotenoid, terpenes and alkaloid with polyphenol being the major chemical group found in both cultivars. It was also revealed that whilst ASR is traditionally consumed in China, Malaysia, Singapore, and Taiwan, indigenous usage of ASG is more common in nations such as Sri Lanka, India, and Indonesia. Both ASG and ASR showed potent anti-oxidant, anti-hyperglycemic, antimicrobial, antifungal and hepatoprotective effects while the anti-inflammatory, anti-cancer and analgesic properties were disclosed in ASG only. Further processing and commercialization of this remedial weed as a product benefiting the wellbeing of humans is recommended as Alternanthera sessilis has high potential to be utilized as a curative agent while being a vital ingredient that can be included in daily consumption.